2017
DOI: 10.1016/s0168-8278(17)31630-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue macrophages induce hepatic neutrophil recruitment and macrophage accumulation in mice

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In obesity, an increased number of activated macrophages in the VAT lead to local chronic inflammation and VAT dysfunction 36,42,43 . Bijnen et al 44 showed that the transplantation of macrophage infiltrated VAT from obese to lean mice was able to induce macrophage recruitment into the liver and NASH development, underlining the role of these cells in the cross‐talk between liver and VAT 44 . Thus, in order to perform an accurate description of phenomena associated with VAT impairment, which could lead to hepatic and extrahepatic metabolic complications of obesity, we measured VAT levels of both netrin‐1 and UNC5B, which is a netrin‐1‐dependent macrophage retention factor secreted in condition of fatty acids accumulation 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In obesity, an increased number of activated macrophages in the VAT lead to local chronic inflammation and VAT dysfunction 36,42,43 . Bijnen et al 44 showed that the transplantation of macrophage infiltrated VAT from obese to lean mice was able to induce macrophage recruitment into the liver and NASH development, underlining the role of these cells in the cross‐talk between liver and VAT 44 . Thus, in order to perform an accurate description of phenomena associated with VAT impairment, which could lead to hepatic and extrahepatic metabolic complications of obesity, we measured VAT levels of both netrin‐1 and UNC5B, which is a netrin‐1‐dependent macrophage retention factor secreted in condition of fatty acids accumulation 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Bijnen and colleagues transplanted VAT from lean, obese, or ATM‐depleted obese mice to lean Ldr −/− mice. ( 38 ) AT transplantation from obese mice resulted in increased liver injury and hepatic inflammation, which was less pronounced in ATM‐depleted transplanted AT. Liver injury was paralleled by increased numbers of circulating and hepatic neutrophils, an effect mainly attributed to increased synthesis of the neutrophil chemotaxis proteins chemokine (C‐X‐C motif) ligands 14 and 16 by ATM.…”
Section: At Inflammation As a Driver Of Nafldmentioning
confidence: 99%
“…Liver injury was paralleled by increased numbers of circulating and hepatic neutrophils, an effect mainly attributed to increased synthesis of the neutrophil chemotaxis proteins chemokine (C‐X‐C motif) ligands 14 and 16 by ATM. ( 38 )…”
Section: At Inflammation As a Driver Of Nafldmentioning
confidence: 99%
“…Seminal studies of obesity have helped us to understand that macrophages secrete TNFα, which further enhances lipolysis, thereby driving metabolic dysfunction ( 61 ). Moreover, when this occurs in the visceral adipose tissue (VAT), collateral damage to nearby organs, such as liver and pancreas, can lead to metabolic dysfunction of these organs ( 62 , 63 ). Regarding the mechanism of MHO, a previous report showed that TNFα can increase Fas expression ( 64 ).…”
Section: Resultsmentioning
confidence: 99%